PERAN MANAJEMEN SYARIAH TERHADAP PENINGKATAN KEPUASAN PELANGGAN PADA RUMAH SAKIT ISLAM DI KOTA SURAKARTA - Sumadi Sumadi (Jurnal Ilmiah Ekonomi Islam, 2017)
This study aims to find customer satisfaction model at Islamic Hospital in Surakarta. The sample in this study is the respondents who have come and treated in the Islamic Hospital in the city of Surakarta. With various limitations, the target object is the community around the solo who ever come to the hotel sharia. The spread of questionnaires is not necessarily done in Islamic Hospital by looking and giving directly to visitors who come to the place of Islamic Hospital. The criteria used are the people around the solo who already know about the Islamic Hospital and have visited the treatment and never stay in the Islamic Hospital which amounted to 57 respondents. The sampling technique in this research is by accidental sampling. Data analysis method used is validity test, reability test, normality test and multiple linear regression analysis test with t test, F test, and coefficient of determination (R2).